Between Imagination and Information: Exploring the Assessment Practices of Literary and Non-Literary Texts on Reading Skills - Melda Fauzia Damaiyanti; Yeti Mulyati (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2025)
Reading skills in literary and non-literary texts play a crucial role in shaping students’ comprehensive literacy competence. This study aims to explore assessment practices implemented by Indonesian language teachers at the senior high school level, focusing on various aspects including assessment goals, implementation timing, assessed components, instruments, indicators, techniques, and challenges in evaluating students’ reading abilities for both literary and non-literary texts. A qualitative descriptive-exploratory method was employed, with data collected through questionnaires involving 60 teacher respondents. The findings reveal that teachers possess an adequate understanding of the functions of literary and non-literary texts in instruction and apply diverse assessment approaches—ranging from objective test items to interpretive tasks and presentations. Literary texts are predominantly assessed reflectively and interpretively, while non-literary texts are evaluated using analytical and logical methods. Nevertheless, teachers still encounter several challenges, such as limited time, a lack of valid and reliable instruments, the absence of operational technical guidelines, and difficulties in assessing higher-order thinking skills. These findings highlight the need for systematic support in reading assessment, such as ongoing professional training, genre-based instrument development, and teacher collaboration within learning communities. This study emphasizes the importance of a systematic and collaborative approach to improving reading assessment practices to align with curricular demands and the goals of literacy development